Penerapan Arsitektur Eko Organik Pada Resort Pantai Di Kabupaten Pacitan - Kurniawan, Muhammad Dicky; Istijanto, Suko; Wilfritz Soaduon Panjaitan, Tigor (Jurnal Etnik: Ekonomi-Teknik, 2024)
The tourism industry and creative economy have had a very good impact on society's growth rate, but the arrival of the pandemic could "kill" the growth of this industry. The application of the Organic Eco Architecture Theme in the development of the Limasan Village Resort Area located on Watukarung Beach, Pacitan Regency, is a recommendation for responding to the Post-Pandemic period to be able to carry out a "New Awakening" for the Tourism Industry and Creative Economy in Pacitan Regency. The method for developing the Hotel Resort, Limasan Beach, Watukarung Beach, Pacitan Regency is an explanation of the development process accompanied by theories and data obtained from literature studies and field studies, so that the process can provide a picture that supports or supports the development object.